Quality of life in patients with multiple myeloma treated with percutaneous vertebroplasty - Omar Jamit Bohsain (Coluna/Columna, 2014)
OBJECTIVE: To determine the quality of life in patients with multiple myeloma treated with vertebroplasty. Multiple myeloma has a prevalence of 1% in all neoplastic diseases and 10% of hematological malignancies. Bone pain is the initial symptom in most cases. METHODS: A series of cases study was conducted. Patients were assessed by the Karnofsky scale to measure its functionality, the WHO analgesic scale to assess the type of analgesic and visual analog scale (VAS) and the Oswestry questionnaire for pain. RESULTS: Of 24 patients, 10 were cases (vertebroplasty) (41.7%) and 14 were controls (conservative) (58.3%), 13 (54.2%) were female and 11 (45.8%) male, with an average age of 60 years (SD = 12) and 63 kg of average weight (SD = 12), mean height of 1.59 cm (SD = 9) and mean body mass index of 24.8 (SD = 3.7). Survival was obtained from the time of diagnosis to death, and 2 (8.3%) patients died within the first 2 years and 1 (4.2%) after 3 years. CONCLUSIONS: Patients with MM who have vertebral fractures are excellent candidates to undergo vertebroplasty, because this represents a greater benefit in their quality of life, which has a direct impact on their level of functionality, giving them greater self-sufficiency and reducing their pain because of the benefits of the thermogenic effect of vertebroplasty.